PROBLEMS OF RESEARCH DEVELOPMENT AND EDUCATION IN KAZAKHSTAN - Kenzhaliyev, Olzhas; Kassymova, Gulzhaina; Tsekhovoy, Alexey; Ilmaliyev, Zhanserik (Pedagogy and Psychology, 2021)
The accelerated development of economies is not possible without the introduction of innovation and the development of the country's scientific and research potential. The scientific and innovative system, represented by the subjects of the relationship, which directly affect the development of the scientific and innovative potential of the country. The end product of the system is the commercialization of research and development activities. The process of technology commercialization itself is a specific project, nevertheless, project management tools are applicable for it, but taking into account the specifics of innovation and with a high risk of failure. The article examines the main problems and barriers to the commercialization of technologies by conducting a sociological survey of participants in the innovation system of the Republic of Kazakhstan. The purpose of the survey was to obtain a holistic picture of the modern situations of the innovation system of Kazakhstan with an attempt to identify the main problems, both in the system as a whole, and in the process in particular. The respondents were direct participants in technology commercialization projects. Also, the article considered the problem of ensuring the educational approach of direct participants in innovative activities. The problem of the low level of education and the degradation of the education system is rising, which directly affects the country's innovation system. On the basis of the work done, recommendations were received on improving the innovation system and the corresponding project approach to the commercialization of technologies.